Effects of visual instructional Materials on Senior Secondary Two Students’ Achievement in Mathematics in Tambuwal Local Government Area of Sokoto State, Nigeria - Nasiru Muhammad Dogondaji; Isah Maccido (Advanced Journal of STEM Education, 2023)
This Research Paper investigated effect of Visual instructional materials on Senior Secondary two students Achievement in mathematics in Tambuwal local Government area of Sokoto state. It was carried out with three research objectives, three research questions and three null-hypotheses were formulated. Quasi-experimental design was adopted which involved two groups: experimental and control groups. The experimental group was taught Mathematics Concepts using visual instructional materials while the control group was taught without any visual instructional materials. Simple randomly sampling technique was used to select the sample from a population of 1,784 students. Data for the study was collected using a researcher made instrument tagged Mathematics Achievement Pre-test and Post-test (MAPP which was validated and reliability index was found to be 0.75. Data collected were analyzed using descriptive statistics to answer research questions and inferential statistics of independent t-test to answer hypotheses. Major findings from the study revealed a significant difference in the academic achievement of students taught mathematics with the use of visual instructional materials when compared with those taught same concepts of mathematics without the use of visual instructional materials. Moreover, the finding showed no significant difference in the academic achievement of boys and girls taught mathematics concepts using visual instructional materials. It was recommended that Visual and other related instructional materials should be provided by the Government in all Secondary Schools for effective teaching and learning of Mathematics concepts in Sokoto state, Nigeria.